2022
DOI: 10.1186/s13690-022-00948-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between mother’s work status and child stunting in urban slums: a cross-sectional assessment of 346 child-mother dyads in Dhaka, Bangladesh (2020)

Abstract: Background A growing literature highlights the increased risk of stunting among children growing up in informal or slum settlements. Despite relatively high rates of female labor force participation in slums, there is limited evidence on relationship between mother’s work participation and nutritional outcomes of children in these settings. Methods We conducted a cross-sectional study in two large slums (Korail and Tongi) of Dhaka and Gazipur, Bang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 52 publications
1
13
1
1
Order By: Relevance
“…It is important to address this issue by providing adequate childcare support measures for working mothers from poor families to ensure that the child’s essential needs are not impacted by the mother’s employment status. 13 Additionally, efforts should be made to increase awareness among working mothers regarding the importance of child health and nutrition. This can be achieved through targeted education and outreach programmes that provide information on proper child feeding practices, hygiene and health-seeking behaviours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to address this issue by providing adequate childcare support measures for working mothers from poor families to ensure that the child’s essential needs are not impacted by the mother’s employment status. 13 Additionally, efforts should be made to increase awareness among working mothers regarding the importance of child health and nutrition. This can be achieved through targeted education and outreach programmes that provide information on proper child feeding practices, hygiene and health-seeking behaviours.…”
Section: Discussionmentioning
confidence: 99%
“… 6 8 10–12 Children in poor households in Bangladesh are more likely to experience stunted growth if their mothers are employed, as there are inadequate day care centres available for the children, leading to insufficient breast feeding. 13 Moreover, evidence suggests that a number of characteristics at the household level, which relate to both children and mothers, can influence childhood stunting. The characteristics of the household head, household food insecurity and lower dietary diversity, household lower-income, household involvement in several earning activities, availability of sanitation facility at home, hand-washing status, family size, religion and receive several types of allowance from government are most often reported to be associated with stunting in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Secara negatif, ibu bekerja mempunyai waktu yang sedikit untuk mengurus anak. Dimana ibu yang tidak bekerja lebih mempunyai banyak waktu ke posyandu untuk mendapat lebih banyak edukasi terkait gizi dan Kesehatan serta pemberian makanan tambahan 22,31 32 . Selain itu anak bawah dua tahun mempunyai ketergantungan lebih besar kepada ibu, daripada anak usia 3-5 tahun.…”
Section: Hasil Dan Pembahasanunclassified
“…15 In addition, the risk of stunting is 36% higher among first-born children of girls under 18 years in South Asia and it has been found that early motherhood remains a key driver of malnutrition. 16…”
Section: Prevalence Of Low Birth Weightmentioning
confidence: 99%
“…15 In addition, the risk of stunting is 36 percent higher among first-born children of girls under 18 years in South Asia and as such, early motherhood is a key driver of malnutrition. 16 Adolescent birth rate in Bangladesh is one of the highest in the world which is 113 per 1,000 live births. 22 The prevalence of exclusive breastfeeding for the first six months of an infant's life is 55 percent.…”
Section: Determinants Of Low Birth Weightmentioning
confidence: 99%